Faktor yang Mempengaruhi Perubahan Laba Perusahan Barang konsumsi Sub Sektor Makanan dan Minuman yang terdaftar di Bursa Efek Indonesia - Agnes Datu Tanantin; Muhammad Irfai Sohilauw; Didit Fachri Rifai (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to determine the effect of sales growth and the inflation rate on changes in profits in consumer goods companies listed on the Indonesian stock exchange. The population in this study totalled 26 companies using the purposive sampling method for the 2017-2021 period. A sample of 11 consumer goods companies listed on the Indonesia Stock Exchange was obtained based on predetermined criteria. The analytical method used is panel data analysis using E-views 12 Software Assistance. The results show that partial sales growth significantly affects profit changes, and the inflation rate has no significant negative effect on profit changes in consumer goods companies listed on the Indonesian stock exchange in the period 2017-2021. In addition to expanding the research variables, further research can consider the sector to be selected as the object of study.